Mutational landscape of B‐cell post‐transplant lymphoproliferative disorders. (17th April 2017) - Menter, Thomas; Juskevicius, Darius; Alikian, Mary; Steiger, Juerg; Dirnhofer, Stephan; Tzankov, Alexandar; Naresh, Kikkeri N.
Summary: It is currently unclear whether post‐transplant diffuse large B‐cell lymphomas (PT‐DLBCL) display a similar genomic landscape as DLBCL in immunocompetent patients (IC‐DLBCL). We investigated 50 post‐transplant lymphoproliferative disorders (PTLDs) including 37 PT‐DLBCL samples for somatic mutations frequently observed in IC‐DLBCL. Targeted Next Generation Sequencing (NGS) using the Ion Torrent platform and a customized panel of 68 genes was performed on genomic DNA. Non‐tumoural tissue was sequenced to exclude germline variants in cases where available. A control cohort of 76 IC‐DLBCL was available for comparative analyses. In comparison to IC‐DLBCLs, PT‐DLBCL showed more frequent mutations of TP53 ( P  =   0·004), and absence of ATM and B2M mutations ( P  =   0·004 and P  =   0·016, respectively). In comparison to IC‐DLBCLs, Epstein–Barr virus (EBV) + PT‐DLBCL had fewer mutated genes ( P  =   0·007) and particularly fewer mutations in nuclear factor‐κB pathway‐related genes ( P  =   0·044). TP53 mutations were more frequent in EBV ‐ PT‐DLBCL as compared to IC‐DLBCL ( P  =   0·001). Germinal centre B cell (GCB) subtype of PT‐DLBCL had fewer mutations and mutated genes than GCB‐IC‐DLBCLs ( P  =   0·048 and 0·04 respectively). Polymorphic PTLD displayed fewer mutations as compared to PT‐DLBCL ( P  =   0·001). PT‐DLBCL differs from IC‐DLBCL with respect to mutations in genes related to DNA damage control and immune‐surveillance, and EBV association is likely to have a bearing on the mutational pattern.